Poverty Alleviation Through Remittances in Bhimdatta Municipality, Kanchanpur - Singh Thakuri, Bir Bahadur (Journal of Durgalaxmi, 2024)
The increasing ease of global integration and advancements in communication technology have accelerated the migration of Nepali youth to foreign countries. This has resulted in a significant rise in remittance inflows from Gulf nations and other regions, making remittances vital to Nepal's local and national economies. This study, titled "Poverty Alleviation Through Remittances in Bheemdatta Municipality, Kanchanpur District," investigates the role of remittances in reducing rural poverty, their socio-economic impact, and the extent of remittance income in the study area. Employing both qualitative and quantitative methods, the research utilizes descriptive, comparative, and analytical designs. Data collection included household surveys, field visits, focus group discussions, and observations as primary sources, complemented by secondary data. A simple random sampling method was employed to select the respondents in the study area. The findings reveal that remittances significantly enhance household conditions by improving housing, education, healthcare, savings, and overall living standards. The study recommends channeling remittance funds into productive sectors like agriculture and business while advocating for vocational training institutions to support skill development. The research underscores remittances' crucial role in poverty reduction and rural development, offering policy insights to foster sustainable poverty alleviation, influence migration policies, and drive economic diversification in Bheemdatta Municipality.